Dampak Kemandirian Finansial, Beban Hutang, dan Strategi Pengelolaan Keuangan terhadap Stabilitas Ekonomi Mahasiswa (Lembaga Pengembangan Kinerja Dosen, 2025)
This study was conducted to explore the influence of financial independence, debt levels, and students' financial management strategies on their economic stability. A quantitative approach was employed using a survey method, involving 50 students from several universities located in Gresik, Bangkalan, Mojokerto, Surabaya, Sidoarjo, and Lamongan. Data were collected through a closed-ended questionnaire and analyzed using descriptive statistics, Pearson correlation, and multiple linear regression with the assistance of SPSS software. The analysis revealed that, collectively, financial independence, debt burden, and financial management strategies have an impact on students’ economic stability, contributing 20.8% as indicated by the coefficient of determination. However, when examined individually, only the financial burden and the effort to earn additional income were found to have a significant influence. Meanwhile, the perception of financial benefits and financial management strategies did not show a significant effect on students' economic stability. These findings suggest that students' economic stability is not solely influenced by internal financial factors, but may also be affected by various external elements not captured in this study. Therefore, it is recommended that further research be conducted with a larger sample size and a broader set of variables to gain a more comprehensive understanding of student financial conditions in Indonesia.